Clinical and Demographic Profiles of Patients Diagnosed as Cough Variant Asthma attended at Tertiary Referral Hospital (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Cough variant asthma is presented with different clinical and demographic characteristics.Objectives: The purpose of the present study was to see the clinico-demographic profiles of cough variant asthma patients.Methodology: This descriptive type of cross-sectional study was carried out in theDepartment of Respiratory Medicine at National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh from September 2014 to August 2015 for a period of one year. Patients presented with cough variant asthma attending in NIDCH were selected as study population. Methacholine challenge test was performed to diagnosis of Cough Variant Asthma. Result: A total number of 50 patients were recruited for this study. The mean age±SD was found 19.1±7.6 years. Male was predominant than female with a ratio of 1.4.:1. Among the study population positive family history of asthma was found in 39.0% cases and associated allergic rhinitis was reported in 58.0% cases. Eczema was associated with 16.0% patients;however, only 4% patients had associate conjunctivitis. Conclusion: In conclusion young male is more commonly affected by cough variant asthma of which majority have family history of asthma. Journal of National Institute of Neurosciences Bangladesh, 2016;2(1):30-33